Menguatkan Iman Kepada Allah SWT Sebagai Asas Pendidikan Aqidah Islam - Luqman Hakim (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Strengthening aqidah through education is a basic need, because aqidah is the main foundation and basis of Islamic teachings. In another example, everything that exists in this universe is a bias from the existence of Allah SWT. belief in the existence of this universe, actually leads to the fact that "to know the universe, you must first know its Creator." Attack after attack against the creed of Muslims today is very massive. Especially from those with a background of secularism, liberalism and dialectical materialism. The right step is Islamization and revealing the original Islamic philosophical thought. As has been stated by Syed Naquib Al-Attas regarding the Islamization of Science, as well as surgery and unpacking the understanding of al-Buthi's dialectical materialistic understanding. According to al-Attas, the biggest challenge facing Muslims is the challenge of knowledge being spread throughout the Islamic world by Western civilization. The solution is that Western science must first be cleansed of elements that are contrary to Islamic teachings, then formulate and combine essential Islamic elements and key concepts so as to produce a composition that summarizes core knowledge. Meanwhile, al-Buthi, said that there must be original Islamic scientific thoughts that are revealed to the younger generation, so that they know the true aqidah and the straight path